1997
DOI: 10.1007/bf00942047
|View full text |Cite
|
Sign up to set email alerts
|

c-myc in bladder cancer Clinical findings and analysis of mechanism

Abstract: The c-myc gene product is known to be involved in the regulation of cell proliferation and differentiation. Altered c-myc gene expression is a common event in a variety of tumors. This study was designed to investigate c-myc overexpression in transitional cell carcinoma (TCC). The first part was designed to investigate the frequency of c-myc overexpression in relation to tumor stage and tumor grade. A second set of experiments was directed at the mechanisms underlying c-myc overexpression in TCC. A total of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…However, muscle invasion was significantly associated (p<0.05) with c-myc expression as 88.23% of invasive tumor patients showed positive c-myc expression. This finding is in agreement with Schmitz-Drager et al [24] who showed that 58% of their patients were c-myc positive. They also revealed that 59% of the positive cases were of muscle-invasive tumors.…”
Section: Discussionsupporting
confidence: 93%
“…However, muscle invasion was significantly associated (p<0.05) with c-myc expression as 88.23% of invasive tumor patients showed positive c-myc expression. This finding is in agreement with Schmitz-Drager et al [24] who showed that 58% of their patients were c-myc positive. They also revealed that 59% of the positive cases were of muscle-invasive tumors.…”
Section: Discussionsupporting
confidence: 93%
“…). Furthermore, c‐MYC overexpression has been observed in urothelial cancer tissues . Thus, c‐MYC is thought to be relevant to drug‐resistance in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A signi®cant role of MDM2 expression in bladder cancer has been suggested in several studies using immunohistochemical MDM2 analyses. Detectable MDM2 expression has been reported in 9 ± 44% of urinary bladder cancers (Ioachim et al, 2000;Jahnson and Karlsson, 2000;Korkolopoulou et al, 1997;Lianes et al, 1994;P®ster et al, 1999Schmitz-Drager et al, 1997;Shiina et al, 1999). Overall, these studies using immunohistochemistry have yielded con¯icting results, some of them linking MDM2 expression to high (Korkolopoulou et al, 1997) or to low (Lianes et al, 1994) grade and stage tumors while others did not ®nd an association (P®ster et al, 2000;SchmitzDrager et al, 1997;Shiina et al, 1999).…”
Section: Discussionmentioning
confidence: 99%